Medication Errors in Outpatient Pediatrics. Issue 5 (September 2016) - Berrier, Kyla
Abstract : Abstract: Medication errors may occur during parental administration of prescription and over-the-counter medications in the outpatient pediatric setting. Misinterpretation of medication labels and dosing errors are two types of errors in medication administration. Health literacy may play an important role in parents' ability to safely manage their child's medication regimen. There are several proposed strategies for decreasing these medication administration errors, including using standardized dosing instruments, using strictly metric units for medication dosing, and providing parents and caregivers with picture-based dosing instructions. Pediatric healthcare providers should be aware of these strategies and seek to implement many of them into their practices. Abstract : An overview of pediatric medication errors in the outpatient setting with a focus on errors in medication administration and the contributing effects of parental health literacy is presented.